Pengaruh Perkembangan Usaha Mikro, Kecil, dan Menengah Terhadap Pendapatan Nasional Pada Sektor UMKM di Indonesia - Lies Maria Hamza; Devi Agustien (Jurnal Ekonomi Pembangunan, 2019)
This study aims to analyze the influence of the development of Micro, Small, and Medium Enterprises on the national income of the UMKM sector in Indonesia. This research used a panel data method with Fixed Effect Model. The data used are secondary in the value of GDP of UMKM, Labours of UMKM, investment of UMKM, and the number of units of UMKM from the 2000-2013 period. The results showed that labors of UMKM and placement of UMKM have a positive and significant effect on the national income of the UMKM sector in Indonesia. While for the number of units of UMKM not affect the national income of the UMKM sector in Indonesia.